Role of Galectin‐3 in the pathophysiology underlying allergic lung inflammation in a tissue inhibitor of metalloproteinases 1 knockout model of murine asthma. Issue 3 (7th November 2017) - Mammen, Manoj J.; Sands, Mark F.; Abou‐Jaoude, Elaine; Aalinkeel, Ravikumar; Reynolds, Jessica L.; Parikh, Neil U.; Sharma, Umesh; Schwartz, Stanley A.; Mahajan, Supriya D.
Summary: Asthma is a chronic inflammatory respiratory disease characterized by airway inflammation, airway hyperresponsiveness and reversible airway obstruction. Understanding the mechanisms that underlie the various endotypes of asthma could lead to novel and more personalized therapies for individuals with asthma. Using a tissue inhibitor of metalloproteinases 1 (TIMP‐1) knockout murine allergic asthma model, we previously showed that TIMP‐1 deficiency results in an asthma phenotype, exhibiting airway hyperreactivity, enhanced eosinophilic inflammation and T helper type 2 cytokine gene and protein expression following sensitization with ovalbumin. In the current study, we compared the expression of Galectins and other key cytokines in a murine allergic asthma model using wild‐type and TIMP‐1 knockout mice. We also examined the effects of Galectin‐3 (Gal‐3) inhibition on a non‐T helper type 2 cytokine interleukin‐17 (IL‐17) to evaluate the relationship between Gal‐3 and the IL‐17 axis in allergic asthma. Our results showed a significant increase in Gal‐3, IL‐17 and transforming growth factor‐ β 1 gene expression in lung tissue isolated from an allergic asthma murine model using TIMP‐1 knockout. Gal‐3 gene and protein expression levels were also significantly higher in lung tissue from an allergic asthma murine model using TIMP‐1 knockout. Our data show that Gal‐3 may regulate the IL‐17 axis and play a pivotal role in the modulation of inflammation during experimental allergic asthma. Abstract : Galectin‐3 may regulate the interleukin‐17 axis and play a pivotal role in the modulation of inflammation during experimental allergic asthma.